Agave Leaves as a Substrate for the Production of Cellulases by Penicillium sp. and the Obtainment of Reducing Sugars - Julio Silva-Mendoza; Alberto Gómez-Treviño; Ulrico López-Chuken; Edgar Allan Blanco-Gámez; Leonardo Chávez-Guerrero; María Elena Cantú-Cárdenas (Journal of Chemistry)
Lignocellulosic biomass can be used to obtain fermentable sugars by enzymatic hydrolysis, and also it serves as a carbon source to produce cellulases by solid-state fermentation. In this study, we propose the use of leaves of Agave salmiana as a carbon source to produce cellulases by the fungus Penicillium sp., isolated from the same plant. The crude enzymatic extract was used to obtain sugars from the hydrolysis of the parenchymal cells of the leaves. The enzymes produced were characterized (endoglucanase 14.4 U/g; exoglucanase 3.5 U/g; β-glucosidase 4.14 U/g). The enzymes showed activities at elevated temperatures: 50°C for endoglucanase and exoglucanase and 70°C for β-glucosidase. Furthermore, the crude enzymatic extract obtained was able to hydrolyze the parenchyma in 51.6% in 48 h. The evidence presented in this paper shows the potential of the agave leaves as a source of carbon in the production of enzymes by fermentation with the consequent production of reducing sugars. In addition, the enzymes produced by Penicillium sp. could be used in the production of bioethanol, since they work at high temperatures.